Interactive Multimedia Development Using Autoplay Media Studio 8 About Diversity of Life Organization System For VII Grade Students of Junior High School - Fitri Ningsih (Journal of Biological Science and Education, 2020)
Learning media is one of the tools that teachers use to deliver material to students, so that they can be motivated in learning. Unfortunately, there are some teachers have not used interesting media in order to increase students interest. In this case, one of the effective media is by used interactive multimedia. Therefore, in this study the researcher try to develop the interactive multimedia by using Auto play Media Studio 8 about the diversity of life organization system for VII grade students. The research subject consisted of three biology lecturers in UNP, two science teachers and 30 students in class VII of SMPN 31 Padang. Based on data analysis, the validity value of 80.81% (valid) is obtained, the practicality value of the teachers was 86.60% (practical) and the practicality value of students was 90.91% (efficient). The conclusion of this study was interactive multimedia was valid and functional to use